IL-10-Dependent and -Independent Mechanisms Are Involved in the Cardiac Pathology Modulation Mediated by Fenofibrate in an Experimental Model of Chagas Heart Disease - Rada, Jimena; Donato, Martín; Penas, Federico N.; Alba Soto, Catalina; Cevey, Ágata C.; Pieralisi, Azul V.; Gelpi, Ricardo; Mirkin, Gerardo A.; Goren, Nora B. (Frontiers in Immunology, 2020)
IL-10 is an anti-inflammatory cytokine that plays a significant role in the modulation of the immune response in many pathological conditions, including infectious diseases. Infection with Trypanosoma cruzi (T. cruzi), the etiological agent of Chagas disease, results in an ongoing inflammatory response that may cause heart dysfunction, ultimately leading to heart failure. Given its infectious and inflammatory nature, in this work we analyzed whether the lack of IL-10 hinders the anti-inflammatory effects of fenofibrate, a PPARα ligand, in a murine model of Chagas heart disease (CHD) using IL-10 knockout (IL-10 KO) mice. Our results show fenofibrate was able to restore the abnormal cardiac function displayed by T. cruzi-infected mice lacking IL-10. Treatment with fenofibrate reduced creatine kinase (CK) levels in sera of IL-10 KO mice infected with T. cruzi. Moreover, although fenofibrate could not modulate the inflammatory infiltrates developing in the heart, it was able to reduce the increased collagen deposition in infected IL-10 KO mice. Regarding pro-inflammatory mediators, the most significant finding was the increase in IL-17 mRNA and serum IL-17. These were reduced in IL-10 KO mice upon fenofibrate treatment. In agreement with this, the expression of RORγT was reduced. Infection of IL-10 KO mice increased the expression of YmI, FIZZ and Manose Receptor (tissue healing markers) that remained unchanged upon treatment with fenofibrate. In conclusion, our work emphasizes the role of anti-inflammatory mechanisms to ameliorate heart function in CHD and shows, for the first time, that fenofibrate attains this through IL-10-dependent and -independent mechanisms.